Penambahan Bahan Additive Grolen DP serta Variasi Umur untuk Meningkatkan Kuat Tekan Beton - Venny Andriani; Ahmad Ridwan; Yosef Cahyo Setianto Poernomo; Ashabul Yamin (Faculty of Engineering, Kadiri University, 2021)
Concrete is a building material that plays an important role in the construction of buildings and bridges. Adding materials to concrete in the current era is increasingly becoming developed because it is able to change the properties of concrete mixtures according to needs. Additive Grolen DP is an added material that can accelerate the hardening of concrete and reduce water consumption. The purpose of this study was to determine the compressive strength and slump value with the addition of additive Grolen DP 0%, 3%, and 7% for variation of age 3, 7, and 28 days. The method used is an experimental method by making test objects that refer to SNI. The specimens used are cylindrical dimensions 15x30 cm with an initial quality plan Fc'= 22.06 Mpa. The results showed that the highest average compressive strength was the addition of additive Grolen DP 7% or BT 3 with a variation of 28 days of age with a value of Fc’= 38.02 MPa. The slump value generated by BT= 11.2 cm. BT 2= 12.3 cm, and BT 3= 12.9 cm. From these results, it can be seen that the addition of variations additive Grolen DP affects the quality of concrete.